Production of Bovine Embryos and Calves Cloned by Nuclear Transfer Using Mesenchymal Stem Cells from Amniotic Fluid and Adipose Tissue - Da Silva, Carolina Gonzales; Martins, Carlos Frederico; Cardoso, Tereza Cristina [UNESP]; Da Cunha, Elisa Ribeiro; Bessler, Heidi Christina; Martins, George Henrique Lima; Pivato, Ivo; Báo, Sônia Nair (SAGE Publications, 2016)
The less differentiated the donor cells are used in nuclear transfer (NT), the more easily are they reprogrammed by the recipient cytoplasm. In this context, mesenchymal stem cells (MSCs) appear as an alternative to donor nuclei for NT. The amniotic fluid and adipose tissue are sources of MSCs that have not been tested for the production of cloned embryos in cattle. The objective of this study was to isolate, characterize, and use MSCs derived from amniotic fluid (MSC-AF) and adipose tissue (MSC-AT) to produce cloned calves. Isolation of MSC-AF was performed using in vivo ultrasound-guided transvaginal amniocentesis, and MSC-AT were isolated by explant culture. Cellular phenotypic and genotypic characterization by flow cytometry, immunohistochemistry, and RT-PCR were performed, as well as induction in different cell lineages. The NT was performed using MSC-AF and MSC-AT as nuclear donors. The mesenchymal markers of MSC were expressed in bovine MSC-AF and MSC-AT cultures, as evidenced by flow cytometry, immunohistochemistry, and RT-PCR. When induced, these cells differentiated into osteocytes, chondrocytes, and adipocytes. Embryo production was similar between the cell types, and two calves were born. The calf from MSC-AT was born healthy, and this fact opens a new possibility of using this type of cell to produce cloned cattle by NT.